Differential effects of antibiotics on neutrophils exposed to lipoteichoic acid derived from Staphylococcus aureus - Marquerita Algorri; Annie Wong-Beringer (BMC, 2020)
Abstract Background Persistent bacteremia occurs in at least 30% of patients with Staphylococcus aureus bloodstream infection (SAB) and may be attributable to a dysregulated host immune response. Neutrophils interact with a variety of S. aureus microbial factors, including lipoteichoic acid (LTA), to activate phagocytic function in a concentration-dependent manner. Antibiotics have been shown to exert both direct antimicrobial action as well as immunomodulatory effects. In this study, we compared the effects of different anti-staphylococcal antibiotics on LTA-mediated immune activation of neutrophils. Methods Neutrophils obtained from healthy volunteers were exposed to two levels of LTA (1 and 10 μg/ml) with or without addition of antibiotics from different pharmacologic classes (vancomycin, daptomycin, ceftaroline). Neutrophil function was assessed by examining phagocytic response, activation (CD11b, CD62L expression), Toll-like receptor-2 expression, cell survival and apoptosis, and CXCL8 release. Results Differential LTA-mediated antibiotic effects on neutrophil function were observed primarily at the high LTA exposure level. Ceftaroline in the presence of 10 μg/ml LTA had the most prominent effects on phagocytosis and CD11b and CD62L expression, with trends towards increased neutrophil survival and preservation of CXCL8 release when compared to daptomycin and vancomycin with the latter significantly dampening PMN CXCL8 release. Conclusions Select antimicrobial agents, such as ceftaroline, exert immunostimulatory effects on neutrophils exposed to S. aureus LTA, which when confirmed in vivo, could be leveraged for its dual immunomodulatory and antibacterial actions for the treatment of persistent SAB mediated by a dysregulated host response.